Toxicological and morphological effects of squamocin and tebufenozide on Anticarsia gemmatalis (Lepidoptera: Noctuidae) larvae - Fiaz, Muhammad (2019)
Anticarsia gemmatalis Hübner (Lepidoptera: Noctuidae) is the main defoliating pest of soybean (Glycine max L. Merrill, FaLO LOURENCO DA SILVAbaceae) in Brazil. There are a variety of plant products and pt-ensynthetic insecticides used to control A. gemmatalis. The larval midgut is reported to be the 'front line' in creation of local immune defense and detoxification of xenobiotic compounds. These characteristics make the midgut cells to be the most affected by those xenobiotics. Squamocin from Annona mucosa and tebufenozide were evaluated to test their toxicity and their ultrastructural effects in midgut cells of A. gemmatalis. Toxicological results showed that A. gemmatalis was susceptible to both squamocin and tebufenozide. Larvae exposed to tebufenozide compromised larval fitness and its survivorship. LC50 and LC90 of squamocin and tebufenozide against A. gemmatalis were 37.14 mg/L-1, 83.14 mg/L-1 and 3.86 mg/L-1, 12.16 mg/L-1, respectively. Squamocin and tebufenozide intake caused deformities in epithelial cells. Squamocin damage to midgut cells include enlarged basal labyrinth, highly vacuolated cytoplasm, damaged apical surface, release of cell protrusions to the gut lumen, autophagy and cell death. Ingestion of tebufenozide caused damage to striated border with release of protrusions to the midgut lumen, damaged nuclear membrane and nucleus with condensed chromatin and increase autophagic vacuolization. Both, squamocin and tebufenozide, damaged mitochondria and compromised respiration rate, while in case of tebufenozide, severe damage resulted in to modification of mitochondria into nanotunnels along with compromising respiration rate. Squamocin and tebufenozide are lethal to larvae, they compromised its fitness and induced severe morphological changes in midgut cells empowering control program against A. gemmatalis.